How to overcome fear and live your life to the fullest - Witt, Marcos; Green berg, Amy; Simon & Schuster Audio (Prince Frederick, MD : Recorded Books, 2007)
The author teaches you that the closer you get to your fears, the more you understand them and the more easily you can defeat them. Speaking from his own experience, Marcos Witt takes readers on a clear path toward following the word of God as a bridge to living a life of victory and freedom, without fear
Title from container
Narrated by the author
Keywords: Fear -- Religious aspects -- Christianity; Audiobooks